USING ACTIVITY BASED COSTING (ABC) IN CUSTOMER PROFITABILITY ANALYSIS (CPA) AND A ACHIEVEMENT THE COMPETITIVE ADVANTAGE : دراسة تطبيقية في شركة الكريستال لصناعة الاصباغ - Thaer Imran Musa; Arshad Makki Rashid (Iraqi Journal for Administrative Sciences, 2024)
The primary purpose of this research is using the activity based costing (Abc) system in customer profitability analysis so that achieve a sets of interest as follows managing the cost and revenues , managing the risk ,as well as, Improvement competitive position ,this research divides to four section : the first section consist of research methodology and previous studies . the two search consist of theoretical bask ground through explain the role of customer profitability analysis in a achieving the competitive advantage by use the activity based costing (Abc) . the three search consist of applied study in company establishment in year 2000 , the number of its customer 42. The research focus for studing the effect on company profitability and achieving the competitive advantage ,as well as, achieving the strategy . the four search consist of conclusions and recommendations , the research showed asset of conclusion , the important of its : the determine the basic factor on profitability will help in manage me the business , and control the relation ship between company and costumed . the applied study conclude the size ( customer revenues ) is a basic in effect on company profitability .